2004
DOI: 10.1128/jvi.78.17.9051-9063.2004
|View full text |Cite
|
Sign up to set email alerts
|

Measles Virus (MV) Hemagglutinin: Evidence that Attachment Sites for MV Receptors SLAM and CD46 Overlap on the Globular Head

Abstract: Measles virus hemagglutinin (MVH) residues potentially responsible for attachment to the wild-type (wt) MV receptor SLAM (CD150) have been identified and localized on the MVH globular head by reference to a revised hypothetical structural model for MVH (www.pepscan.nl/downloads/measlesH.pdb). We show that the mutation of five charged MVH residues which are conserved among morbillivirus H proteins has major effects on both SLAM downregulation and SLAM-dependent fusion. In the three-dimensional surface represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 54 publications
2
57
1
Order By: Relevance
“…Unlike fusion or other multifunctional proteins, where N-glycans play an important role in activation (2,8,16,26,30,40,47), the paramyxovirus attachment protein does not require cleavage to be functional. Despite this, sialic acid-binding attachment proteins are more sensitive to N-glycan deletion than CDV H (27,31,39), suggesting that their N-glycans may be involved in receptor recognition and attachment, while N glycosylation has not been demonstrated to play a role in morbillivirus interaction with its protein receptors SLAM and CD46 (4,7,18,25,46,49). The observation that a completely deglycosylated H protein remains functional thus indicates a correlation between the Nglycosylation requirement and the folding and processing complexity of glycoproteins.…”
Section: Resultsmentioning
confidence: 85%
“…Unlike fusion or other multifunctional proteins, where N-glycans play an important role in activation (2,8,16,26,30,40,47), the paramyxovirus attachment protein does not require cleavage to be functional. Despite this, sialic acid-binding attachment proteins are more sensitive to N-glycan deletion than CDV H (27,31,39), suggesting that their N-glycans may be involved in receptor recognition and attachment, while N glycosylation has not been demonstrated to play a role in morbillivirus interaction with its protein receptors SLAM and CD46 (4,7,18,25,46,49). The observation that a completely deglycosylated H protein remains functional thus indicates a correlation between the Nglycosylation requirement and the folding and processing complexity of glycoproteins.…”
Section: Resultsmentioning
confidence: 85%
“…Previous studies on the receptordependent fusion-inducing activity of mutant MV-H proteins identified several amino acid residues important for interaction with SLAM: D505, D507, Y529, D530, T531, R533, F552, Y553 and P554 (23,24) (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
“…2). On the other hand, the key residues for interaction of MV-H (Ed) with CD46 (23,24,28) span the ␤3 to ␤5 sheets of the side face of the head domain and are located differently from the key residues at the SLAM-binding site (Fig. 3B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed, Ile-194, Tyr- 529, Asp-530, Thr-531, Arg-533, Tyr-553, and Pro-554 were identified based on a receptor-dependent fusion assay (15). Asp-505, Asp-507, and His-536 were initially shown only to significantly reduce SLAM-down-regulation (33). We have subsequently tested D505G and D507G mutations in a receptor-specific cell-to-cell fusion assay and confirmed that they cause a two-third decrease in SLAM-dependent fusion (data not shown).…”
Section: Discussionmentioning
confidence: 99%